2019
DOI: 10.1002/cbin.11085
|View full text |Cite
|
Sign up to set email alerts
|

RASSF1‐AS1, an antisense lncRNA of RASSF1A, inhibits the translation of RASSF1A to exacerbate cardiac fibrosis in mice

Abstract: Cardiac fibrosis is associated with various cardiovascular diseases and can eventually lead to heart failure. Dysregulation of long non‐coding RNAs (lncRNAs) are recognized as one of the key mechanisms of cardiac diseases. However, the roles and underlying mechanisms of lncRNAs in cardiac fibrosis have not been explicitly defined. Here, we investigated the role of an antisense (AS) lncRNA from the Ras association domain‐containing protein 1 isoform A (RASSF1A) gene locus, named RASSF1‐AS1, in the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Long noncoding RNAs (lncRNAs), which are a recently discovered class of noncoding RNAs, are transcribed from noncoding sequences in the genome, are longer than 200 nt and do not have the ability to be translated into proteins (10,11). LncRNAs have become a novel research focus since numerous lncRNAs have been discovered that are closely related to the occurrence of a great number of diseases due to their extensive regulatory effects on epigenetics (12), transcription (13), and protein translation (14) and modification (15). Therefore, a systematic study of the regulatory role of lncRNAs in the pathogenesis of RA will help in more comprehensively understanding the mechanism of RA and providing new insight and targets for its clinical diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs), which are a recently discovered class of noncoding RNAs, are transcribed from noncoding sequences in the genome, are longer than 200 nt and do not have the ability to be translated into proteins (10,11). LncRNAs have become a novel research focus since numerous lncRNAs have been discovered that are closely related to the occurrence of a great number of diseases due to their extensive regulatory effects on epigenetics (12), transcription (13), and protein translation (14) and modification (15). Therefore, a systematic study of the regulatory role of lncRNAs in the pathogenesis of RA will help in more comprehensively understanding the mechanism of RA and providing new insight and targets for its clinical diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The lncRNA RASSF1-AS1 encoded by the antisense strand of the RASSF1A gene was significantly overexpressed in the isoproterenol (ISO)-induced mice model. RASSF1-AS1 binds to RASSF1 mRNA to promote NF-κB activation and inhibit the translation of RASSF1A, thus exacerbating myocardial fibrosis in mice, indicating a potential application of RASSF1-AS1 as a therapy target for myocardial fibrosis [ 42 ]. The expression of myocardial specific lncRNA Colorectal Neoplasia Differentially Expressed (CRNDE) is negatively correlated with the expression of genes related to myocardial fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Many NATs are described as lncRNAs without information about the co-existence of other transcripts from the same genomic origin [12]. Currently, antisense lncRNAs have been reported to regulate cell proliferation and differentiation [13]. Furthermore, we have previously demonstrated that lncRNA zinc finger E-box binding homeobox 1 (ZEB1) antisense RNA1 could facilitate EMT by regulating miR-141-3p/ZEB1 axis in IPF rats [14].…”
Section: Introductionmentioning
confidence: 99%